Sharing or not sharing online video on social media - Crespel, Elodie (My University, 2013)
The phenomenon of the social web (Web 2.0) and the proliferation of devices that are always connected to the Internet, such as smartphones, are transforming Internet studies. Nowadays, studying online and offline activities separately is unthinkable, since the Internet plays such a great part of everyday life (boyd & Ellison, 2007). The same is true about computer and telephone. For example, user can start an email on their smart phone and finish it on their computer. Reflecting on abundance of online audio-visual content, several questions may be raised: How certain video become viral? Why do people want to share certain type of video? For this paper, I will use my current work for my PhD thesis that explores the role of online videos in interpersonal communications and groups of users. Videos are an unavoidable Internet phenomenon (Purcell, 2010). Videos move from one site to another, from computer to phone, they are spread through word of mouth, and broadcast on television. This paper examines how people decide to post a video on their Facebook wall or friend’s wall. It shows that it can be done to share information, a feeling or an experience. Each individual has a unique practice and motivation for sharing online video, whether through a social networking site, by email, showing it directly to a friend and family member. This paper aims to better understand why ordinary people share online videos via social networking sites. The data used in this paper is from semi-structured and open interviews. I proceed by conducting three interviews per participant, allowing the construction of a dialogue. During the first interview, I asked participants to simply describe their everyday experiences related to online videos. A second interview allows me to elaborate on some details. The last meeting is directly inspired by the notion of reflective practices (Finlay, 2002) and I make a first analysis of previous meetings. Thus, researcher and participant discuss the initial interpretations and the research process.
Keywords: online video; sharing; everyday life; Facebook; emotion